Fast Facts: Colorectal Cancer - Taylor, Irving; Ward, Robin (S. Karger, 2010)
Early detection is essential if patients are to be offered the best chance of survival from colorectal cancer. Many of the genetic and environmental factors that contribute to the development of this disease are now well recognized. In addition, new drug therapies have changed the way colorectal cancer is treated.'Fast Facts: Colorectal Cancer' delivers concise and highly practical information on all aspects of this all too common disease. This fully updated third edition provides invaluable information for the primary care team, who are key to the screening and diagnosis of the disease, and essential to the provision of optimal support services.Written by three international specialists, this new edition has been substantially revised and expanded, and includes: • Discussion of the latest therapeutic developments in both the adjuvant and metastatic setting• Updated information on the genetic factors that contribute to development of the disease• Expert guidance on diagnosis, screening and treatmentsContents:• Epidemiology and pathophysiology• Clinical presentation• Diagnosis and staging• Screening and surveillance• Treatment of the primary disease• Large bowel obstruction• Advanced and recurrent disease• Multidisciplinary management• Future trends• Useful Resources
Keywords: Colorectal Neoplasms; kolorektální nádory; gastroenterologie; Gastroenterology; onkologie